2009
DOI: 10.5580/25bc
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy Of Topical Lignocaine Spray (10%) Applied Before The Induction Of Anaesthesia In Attenuating The Pressor Response To Direct Laryngoscopy And Endotracheal Intubation In Controlled Hypertensive Patients

Abstract: We evaluated the efficacy of topical lignocaine spray (10%) applied prior to induction of anaesthesia in attenuating the pressor response to laryngoscopy and endotracheal intubation in 50 controlled hypertensive patients, undergoing different elective surgical procedures under general anaesthesia. Patients were allocated randomly to one of the 2 groups of 25 patients each. Group I received lignocaine 10 % oral spray 2 minutes prior to induction of anesthesia for a total of 10 puffs (100 mg).Group II received n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…While in other group they performed only one laryngoscopy and hence noxious stimuli were given twice in the topical group.Mostafa 16 and Hamill 17 in their respective studies had concluded that topical lignocaine is ineffective in preventing the pressor response. Takita etal 18 suggested that differing intervals between tracheal lignocaine and endotracheal intubation probably caused the inconsistent conclusion reported in other investigations and showed that endotracheal intubation performed two minutes after tracheal lignocaine attenuated the cardiovascular responses to endotracheal intubation M. Jain et al 19 performed a study on lignocaine 10 percent spray to study its efficacy in attenuating the pressor response and found it to be effective in attenuating and not abolishing the response, we had similar findings in lignocaine being able to attenuate the pressor response, but they didn't study the optimal timing of the spray and they didn't use glycopyrrolate as a premedication.…”
Section: Discussionmentioning
confidence: 96%
“…While in other group they performed only one laryngoscopy and hence noxious stimuli were given twice in the topical group.Mostafa 16 and Hamill 17 in their respective studies had concluded that topical lignocaine is ineffective in preventing the pressor response. Takita etal 18 suggested that differing intervals between tracheal lignocaine and endotracheal intubation probably caused the inconsistent conclusion reported in other investigations and showed that endotracheal intubation performed two minutes after tracheal lignocaine attenuated the cardiovascular responses to endotracheal intubation M. Jain et al 19 performed a study on lignocaine 10 percent spray to study its efficacy in attenuating the pressor response and found it to be effective in attenuating and not abolishing the response, we had similar findings in lignocaine being able to attenuate the pressor response, but they didn't study the optimal timing of the spray and they didn't use glycopyrrolate as a premedication.…”
Section: Discussionmentioning
confidence: 96%
“…Hence, Effective attenuation of haemodynamic surge has become an important part in modern anesthesiology and various pharmacological methods have been tried for this. A wide variety of drugs are used to attenuate the hemodynamic response of laryngoscopy and intubation like Lignocaine [4,[6][7][8][9][10][11][12][13][14][15][16][17][18] , fentanyl [19][20][21][22][23] , alfentanyl, ramifentanyl [24] nifedipine [25] , beta blockers like, labetalol [26] , metoprolol, esmolol, gabapentin, pregabalin, magnesium sulphate, ivabradine, dexmedetomidine [27] , cloning [28] . Lignocaine is an aminoethylamide and prototype of amide local anesthetic group.…”
Section: Introductionmentioning
confidence: 99%